Gambaran Kesiapan Puskesmas Cipatujah dalam Menerapkan Rekam Medis Elektronik dengan Instrumen CAFP Tahun 2024 - Nurholisoh, Iis; Fadly, Fery; Junaedi, Fadil Ahmad; Suryani, Dewi Lena (Indonesian of Health Information Management Journal (INOHIM), 2025)
Abstract The Electronic Medical Record (EMR) requires organizational readiness prior to implementation, one of which can be assessed using the California Academy of Family Physicians (CAFP) instrument. This study aims to describe the readiness level of Cipatujah Public Health Center in implementing EMR in accordance with Regulation of the Minister of Health of the Republic of Indonesia Number 24 of 2022. A quantitative descriptive design was employed with a total sampling technique involving 50 health center staff. Readiness was assessed across five domains (management capacity, financial and budget capacity, operational capacity, technological capacity, and organizational alignment) based on the average scores of the CAFP instrument. The results show that management capacity obtained a score of 13.52 (range II), indicating moderate readiness but highlighting the need to strengthen human resources in medical records and IT. Financial and budget capacity (13.86), operational capacity (14.26), technological capacity (28.34), and organizational alignment (29.2) were in range I, reflecting strong readiness supported by adequate budgeting, infrastructure, workflows, and the commitment of leadership and staff. Overall, Cipatujah Public Health Center is categorized as highly ready for EMR implementation, although improvements in management aspects and the addition of supporting personnel remain necessary. Keyword: Preparedness, Electronic Medical Records, CAFP, Puskesmas Abstrak Rekam Medis Elektronik (RME) menuntut kesiapan organisasi sebelum diimplementasikan, salah satunya dapat diukur menggunakan instrumen California Academy of Family Physicians (CAFP). Penelitian ini bertujuan menggambarkan tingkat kesiapan Puskesmas Cipatujah dalam penerapan RME sesuai mandat Permenkes RI Nomor 24 Tahun 2022. Penelitian menggunakan desain kuantitatif deskriptif dengan teknik total sampling terhadap 50 petugas Puskesmas. Penilaian dilakukan pada lima domain kesiapan (kapasitas manajemen, keuangan dan anggaran, operasional, teknologi, dan keselarasan organisasi) berdasarkan skor rata‑rata instrumen CAFP. Hasil menunjukkan kapasitas manajemen memperoleh skor 13,52 (range II) yang menandakan kesiapan cukup namun masih memerlukan penguatan SDM rekam medis dan IT. Kapasitas keuangan dan anggaran (13,86), operasional (14,26), teknologi (28,34), dan keselarasan organisasi (29,2) berada pada range I yang mencerminkan kesiapan kuat dengan dukungan anggaran, infrastruktur, alur kerja, serta komitmen pimpinan dan staf. Secara keseluruhan, Puskesmas Cipatujah dikategorikan sangat siap untuk penerapan RME, meskipun peningkatan pada aspek manajemen dan penambahan tenaga pendukung tetap diperlukan. Kata Kunci: Kesiapan, Rekam Medis Elektronik, CAFP, Puskesmas